Treatment of Acne Keloidalis Nuchae: A Systematic Review of the Literature. Issue 3 (September 2016) - Maranda, Eric; Simmons, Brian; Nguyen, Austin; Lim, Victoria; Keri, Jonette
Abstract Acne keloidalis nuchae (AKN) is a chronic inflammatory condition that leads to fibrotic plaques, papules and alopecia on the occiput and/or nape of the neck. Traditional medical management focuses on prevention, utilization of oral and topical antibiotics, and intralesional steroids in order to decrease inflammation and secondary infections. Unfortunately, therapy may require months of treatment to achieve incomplete results and recurrences are common. Surgical approach to treatment of lesions is invasive, may require general anesthesia and requires more time to recover. Light and laser therapies offer an alternative treatment for AKN. The present study systematically reviews the currently available literature on the treatment of AKN. While all modalities are discussed, light and laser therapy is emphasized due to its relatively unknown role in clinical management of AKN. The most studied modalities in the literature were the 1064-nm neodymium-doped yttrium aluminum garnet laser, 810-nm diode laser, and CO2 laser, which allow for 82–95% improvement in 1–5 sessions. Moreover, side effects were minimal with transient erythema and mild burning being the most common. Overall, further larger-scale randomized head to head control trials are needed to determine optimal treatments.